Health Literacy among Pregnant Women Who Have Gestational Diabetes Mellitus - Sripoun, Sureepron; Samphan, Rungtawin; Srewongchai, Lumpong; Discharoen, Kruawan (Nursing Journal of The Ministry of Public Health, 2024)
Gestational diabetes is the most common pregnancy complication that affects maternal and neonatal health due to maternal poor glycemic control, resulting from a lack of knowledge and health management. This descriptive research aimed to study the level of health literacy and factors related to the health literacy of gestational diabetes. The participants consisted of 105 pregnant women diagnosed with gestational diabetes in Phontong, Salaphum Hospital, Roi -Et province, and Yasothon Hospital,Yasothon province. These participants were selected by purposive sampling. Data were assessed by the 4-dimension health literacy questionnaire, which has an index of item objective congruence of .93 and a Cronbach’s alpha coefficient of .98. The data were analyzed using descriptive statistics and Spearman’s correlation coefficient. The results showed that the overall mean of health literacy among pregnant women was at a fair level (mean=72.63, SD=15.63). The level of health literacy in the dimension of self-management of health was the lowest (mean=70.64, SD=16.94). Regarding the factors related to the health literacy of gestational diabetes, it was found that the level of education positively correlated with health literacy at a low level (r=.34, p<.05). Therefore, to enhance the ability of pregnant women with gestational diabetes, health personnel should establish health services to promote self-management of health, especially for those who have a low level of education.